Attachement Territorial, Fierté D’habiter Et Développement Local - Pascaru, Mihai (European Scientific Journal, ESJ, 2017)
In a synthetic way, this paper show the results of surveys on how the issues of territorial attachment and of the pride of residing in a specific area, in particular, are associated with respondents’ attitudes, opinions, and life projects. Despite the fact that the investigation is not very current, it is only on this occasion that the analysis is formulated for the first time. A series of conclusions and theoretical and methodological perspectives could position the paper as a possible starting point towards further research and in-depth study on the issue.